2018
DOI: 10.29271/jcpsp.2018.12.914
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Chinese Patients with Hepatocellular Carcinoma (HCC) undergoing Transcatheter Arterial Chemoembolization (TACE) with or without Prophylactic Antibiotic Therapy

Abstract: Objective: To assess the necessity of prophylactic antibiotic therapy in HCC patients undergoing transcatheter arterial chemoembolization (TACE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The need for prophylactic use of antibiotics before c-TACE is consistent with the previous research results [ 18 , 28 , 29 ]. The risk factors for postoperative infection, such as diabetes history [ 19 ] and preoperative serum albumin level [ 15 ], are also consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The need for prophylactic use of antibiotics before c-TACE is consistent with the previous research results [ 18 , 28 , 29 ]. The risk factors for postoperative infection, such as diabetes history [ 19 ] and preoperative serum albumin level [ 15 ], are also consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that prophylactic antibiotics reduce the incidence of liver abscess formation in patients with bile duct injury (29,30). Moreover, previous studies have shown that the incidence of liver abscess formation does not increase among patients without bile duct injury who do not receive prophylactic antibiotics (30,31). Therefore, stratification according to risk factors is more reasonable for the administration of prophylactic antibiotics before TACE.…”
Section: Discussionmentioning
confidence: 99%
“…In the hepatologist survey, 49.1% of the respondents used prophylactic antibiotics for all or selected cases. Although small retrospective studies showed negative results, 26 , 27 a recent large-scale cohort with propensity score analysis demonstrated that prophylactic antibiotics reduced the occurrence of liver abscess following TACE by two-thirds. 28 …”
Section: Prophylactic Medications For Infection and Postembolization ...mentioning
confidence: 99%